Transmedia technologies: theoretical foundations and use in a communication environment (Herald of Journalism, 2019)
In the era of rapidly evolving information technologies, the study of strategies of different media with their nature and features has great importance for understanding the trends in the functioning of digital media and predicting their future development.The purpose of this article is to identify and study the problems of transmedia storytelling in the do- mestic media space. Analysis of its role in the development of information technology and new media systems.The scientific and practical value of the study is to determine the importance of transmedia strategies in the digital age, the study of its conceptual foundations. It is becoming difficult to predict the trends  in the development of new media, since the digital content of the communications technology is hap- pening too quickly.In the course of the analysis of the designated topic, along with such empirical methods as descrip- tion, control, and comparison, theoretical approaches based on the axioms of foreign scientists were used.The main results of a scientific article are: analysis of transmedia strategies in the media space of Kazakhstan, familiarization with the features of communication phenomena; identifying the importance of transmedia strategies and transmedia storytelling, their influence through the communication system on media development.The value of the article. The article analyzes and systematizes the scientific concepts of internation- ally recognized experts in transmedia technologies and transmedia storytelling. The stages of develop- ment of the information and communication sphere of Kazakhstan are also analyzed.The author used various scientific methodologies necessary for the effective identification and pre- diction of political and communication processes in the world. The article was written with the aim of promoting research on the development of the state and society, the preservation of national identity in  the era of information and technological transformation.
Keywords: transmedia strategies, trends in digital media, transmedia, transmedia storytelling, psy- chological manipulations, concept of simplification.